Qualification Strategies and new Media for Quality Assurance in Manufacturing - the example for automotive industry in Korea and Germany - Lee, Young-Hyun [Verfasser]; Lee, Dong-Im [Verfasser]; Härtel, Michael [Verfasser]; Zinke, Gert [Verfasser] (Bundesinstitut für Berufsbildung, 2006)
"This study looks at examples of initial and continuing vocational education and training in the automotive industry in Germany and Korea. It demonstrates the different approaches of the Korean Research Institute for Vocational Education and Training (KRIVET) and the German Federal Institute for Vocational Education and Training (BIBB) in the context of their exploratory research. Whereas KRIVET placed greater value on a thorough treatment of enterprise-based initial and continuing vocational education and training, exemplified by Hyundai Motors, BIBB favoured a composite analysis of four company case studies from the same industry, which drew attention to current initial and further training practices in the companies concerned, highlighting both common features and differences. The results of the joint study highlight the differences in occupational and employment systems, cultural contexts and structural conditions. While the Korean vocational education and training system is primarily school-focused and companies have little involvement in initial and continuing vocational training, in Germany both school-based and dual forms of initial vocational training are found. In the continuing education and training sector in Germany, enterprise-based concepts make a major contribution. The challenges faced by both countries, however, in terms of the global competitive environment and the transition towards a knowledge and information society, are entirely comparable." (BIBB)
Keywords: S 1.3.1 Ausbildung im Dualen System; S 1.5.3 Betriebliche Weiterbildung; L 4.2.3 Internetbasiertes Lernen / E-Learning; G 1.2.4.1 Produktion und Gewinnung; T 1.5 International vergleichende Berufsbildungsforschung; I 2.3.4 Asien; I 2.1 Deutschland; Betriebliche Berufsausbildung; Betriebliche Weiterbildung; Qualifikationsentwicklung; Automobilindustrie; E-Learning; Qualitätssicherung; Fallstudie; Berufsbildungssystem; Internationaler Vergleich; Korea; Bundesrepublik Deutschland